Oxide scale modelling in hot rolling: assumptions, numerical techniques and examples of prediction - Krzyzanowski, M.; Rainforth, W. M. (Ironmaking & steelmaking, 2010)
Oxide scale behaviour in thermomechanical processing has been the subject of intensive research for several years that allowed development of a finite element based model to simulate a range of events of relevance to the process and to the surface quality of the hot rolled product. Oxide scale failure is predicted taking into account the main physical phenomena, such as stress directed diffusion, fracture and adhesion of the oxide scale, strain, strain rate and temperature. The most critical parameters for scale failure are measured during modified hot tensile testing and depend on the morphology of the particular oxide scale and scale growth temperature and are also very sensitive to the chemical composition of the underlying metal. Provided that it is validated, the model can also be used for detailed modelling of the microevents during technological operations. The work integrates finite element analysis with a range of experiments each to provide partial insight into oxide fracture, friction, heat transfer, pick-up and descaling, among others. An overview of this research is presented, revealing a variety of phenomena of considerable technological importance.